Corneal Ulcers with NOD2 Mutations Presenting with Mixed Syndromic Phenotype. (2nd January 2023) - Schofield, Travis Scott; Sup Lee, Chang; Peppers, Brian Patrick; Mauger, Thomas
ABSTRACT: Purpose: To report a case of corneal ulcers in a patient with NOD2 mutations unique to but phenotypically resembling well-characterized syndromic phenotypes like Blau syndrome. Observation: A 25-year-old female with a medical history of type I diabetes mellitus, Asperger syndrome, and neuropathy presented with bilateral corneal ulcers. Her visual acuity was 20/200 OU. Macular edema was identified OS, and posterior synechiae OS suggested a history of anterior uveitis. Genetic testing confirmed NOD2 mutations, and her tear film was positive for matrix metallopeptidase 9. Recent intravenous immunoglobulin therapy improved her neuropathy, and an aggressive regimen of erythromycin ointment and lubrication has improved her ophthalmic symptoms. Conclusion and Importance: This case advances our understanding of NOD2's role in regulating inflammatory processes of the eye. In addition to precipitating uveitis, patients with these mutations may also be at increased risk of developing corneal pathology related to their reduced capacity to moderate inflammatory processes.